2021
DOI: 10.1080/09687637.2021.1916439
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the dark web: navigating the risks of cannabis supply over the surface web

Abstract: Common depictions of buying and selling illicit drugs online centre on how drug market actors engage in dark web drug cryptomarkets, but the supply of illicit drugs also takes place in 'plain site' on the surface web. Drawing on netnographic observations and qualitative interviews with hard-to-reach buyers and vendors (n = 20), this paper explores LeafedOut, a specific, popular surface web platform, that provides a conduit for local cannabis exchanges.We found that the platform enabled easy access and supply a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 78 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…39 DWMs are also communication platforms, where users can meet and chat with other users either directly -using Whatsapp, phone, or email -or through specialised forums. These direct interactions may favour the emergence of decentralised trade networks that bypass the intermediary role of the marketplace, similar to what is currently happening on Facebook, Telegram, and Reddit, [16][17][18][19][20]23 where users post products, negotiate item prices, and then trade directly without an intermediary. We estimate that the trading volume of U2U pairs meeting on DWMs is increasing, reaching a peak in 2020 (during the COVID-19 pandemic).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 DWMs are also communication platforms, where users can meet and chat with other users either directly -using Whatsapp, phone, or email -or through specialised forums. These direct interactions may favour the emergence of decentralised trade networks that bypass the intermediary role of the marketplace, similar to what is currently happening on Facebook, Telegram, and Reddit, [16][17][18][19][20]23 where users post products, negotiate item prices, and then trade directly without an intermediary. We estimate that the trading volume of U2U pairs meeting on DWMs is increasing, reaching a peak in 2020 (during the COVID-19 pandemic).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, some recent works have shown that a significant number of DWM users trade drugs and other illicit goods using social media platforms, such as Facebook, Telegram, and Reddit. [16][17][18][19][20] Moreover, several qualitative, interview-based studies have shown that DWM users form direct trading relationships with other users, starting user-to-user (U2U) pairs that bypass the intermediary role of DWMs. 21,22 Past research has also found that sellers on regulated online marketplaces and social medial platforms may decide to use intermediaries, such Facebook groups or Instagram, to find new customers, and may start direct U2U trading with potential buyers.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent articles explore innovative digital drug market trends combining different platforms on the dark- and surface web. Childs et al (2021) study explored the use of the surface website LeafedOut as a means of connecting local illegal cannabis buyers and sellers in Melbourne, Sydney and Brisbane, with transactions often completed via encrypted apps. Additionally, Barratt et al (2021) analyzed the use of the darknet/encrypted app hybrid platform Televend, which lets vendors manage sales via the darknet using a “shopbot,” which interfaces with customers making purchases via the encrypted app Telegram.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, other important changes in the digital media and communications landscape were occurring. Messaging apps, in particular those that offered encrypted messaging services and real-time mobile group messaging (Baulch et al, 2020;Ling, 2017;Nobari et al, 2021), as well as social media services that facilitated interaction and the sharing of user-generated content (McCay-Peet and Quan-Haase, 2016), afforded new possibilities for drug trading (Blankers et al, 2021;Childs et al, 2021;Demant et al, 2019;Li et al, 2019;McCulloch and Furlong, 2019;Moyle et al, 2019;Oksanen et al, 2021;Shah et al, 2021;van der Sanden et al, 2021), alongside the dramatic rise in social media use (Auxier and Anderson, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite offering advantages when compared with in-person drug sourcing methodsidentified by cryptomarket buyers as wider range, better quality, convenience, and predictability (Bancroft and Scott Reid, 2016;Barratt et al, 2014)-the specialised knowledge required to successfully complete a cryptomarket drug purchase restricts its appeal to specific sub-populations (Childs et al, 2021;Kowalski et al, 2019). This specialised knowledge-accessing the darknet, acquiring and managing cryptocurrencies, and learning to use encryption software-is not required for participation in app markets (McCulloch and Furlong, 2019;Moyle et al, 2019).…”
Section: Introductionmentioning
confidence: 99%